Study of Manufacture of Virgin Coconut Oil by Freezing Method - Panpanya, Supamas (วารสารสมาคมวิศวกรรมเกษตรแห่งประเทศไทย, 2016)
The objectives of this research was study the potential of freezing method on coconut oil – coconut milk a separating process. studying the temperature and the time in Freezing temperatures to freezing at -18, -28 and -38°C, and the time at 36, 40, 44, 48 and 52 hr, respectively, frozen coconut milk was brought to melt at a temperature of 50° C for 1, 1.5, 2 and 2.5 hr, the study found that the temperature and time of freezing can damage the internal structure of the protein bonds. Resulting in delamination of milk after the melt is divided into 3 layers oil layer of cream and a layer of water, while the results of the study showed that the size of the frozen at more than 48 hr resulted increasing amounts of coconut oil every stage in Freezing temperatures.